ANALISIS UNSUR PEMBENTUK FILM ANIMASI FATE/STAY NIGHT: HEAVEN’S FEEL - Prayoga, Ayoung Rega; Runturambi, Raya Nicholas Dewantoro; Shadana, I Gusti Ngurah Dharma; Besin, Enjelita Maria Petricia Yohandra; Janottama, I Putu Arya (Pusat Penerbitan LPPM ISI Bali, 2023)
The Fate/Stay Night franchise and the original visual novels that are the source of the film's story. Fate/Stay Night is a media franchise developed by Type-Moon, a Japanese game development company. The franchise was first introduced through a visual novel released in 2004. This visual novel consists of three main routes, namely Fate, Unlimited Blade Works, and Heaven's Feel. Each route has a different story, with different characters and conflicts. This animation received the 2018 Crunchyroll Anime Award and received a rating of 8.18. I used two methods in this study, namely literature study and observation. The literature study method is carried out by studying book references, articles, and browsing the internet as well as reviewing literature related to system analysis. Analysis of these elements shows that the film has an interesting storyline, as well as presenting themes that can give a message to the audience.